Revised classification of the New World Cylapini (Heteroptera: Miridae: Cylapinae): taxonomic review of the genera Cylapinus, Cylapoides and Peltidocylapus and a morphology-based phylogenetic analysis of tribe Cylapini - Wolski, Andrzej (Zootaxa, 2021)
Cylapini, as currently circumscribed, is a relatively small group of plant bugs currently comprising 17 genera and 65 species. Most representatives of the tribe are distributed in the New World (10 genera and 47 species) with other members occurring in the Afrotropical, Oriental, and Australian regions. They have primarily tropical and subtropical distributions with only a few members inhabiting temperate regions. This paper provides a taxonomic review of three of the New World Cylapini genera: Cylapinus Carvalho, 1986, Cylapoides Carvalho, 1952, and Peltidocylapus Poppius, 1909. Most species are diagnosed and redescribed. Eight new species are described as new: Cylapinus yasunagai sp. nov., Peltidocylapus calyciformis sp. nov., P. caudatus sp. nov., P. ecuadorensis sp. nov., P. pallidus sp. nov., P. parallelus sp. nov., P. simplex sp. nov., and P. spinosus sp. nov. Cylapus festinabundus Bergroth, 1922 is transferred to Peltidocylapus (comb. nov.). Illustrations of male genitalia, scanning electron micrographs of selected structures of certain species, and an identification key of the genera Cylapinus, Cylapoides and Peltidocylapus are provided. Female genitalia are described and illustrated for the first time for most genera of Cylapini. A cladistic analysis of the tribe based on 81 morphological characters is presented as a contribution to the understanding of the ingroup relationships of Cylapini and its relationships with other groups of Cylapinae. The analysis comprises 30 ingroup species and 15 outgroup species. Both equal- and implied weighting parsimony analyses were used in the phylogenetic reconstruction. This analysis was based solely on morphological characters because an insufficient number of specimens suitable for molecular studies were available for most taxa. The study confirmed a close affinity of the taxa currently included in Cylapini, but the tribe was rendered paraphyletic by inclusion of the tribe Vanniini. The grouping comprising both Cylapini + Vanniini and most of its subordinated clades received low nodal support. Both analyses recovered a decisively supported clade comprising the New World genera Amapacylapus, Cylapus, Peltidocylapus, and Valdasus which accommodate most of the Cylapini species, justifying the recognition of the Cylapus complex suggested by previous authors. The results presented here are discussed and compared with previous phylogenetic hypotheses based on different datasets.